2013
DOI: 10.5507/euj.2013.009
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Physical Activity Among Czech and American Children With Hearing Impairment

Abstract: Research is scarce in relation to using social-cognitive theory inclusive of social-cognitive, affective and environmental constructs to predict physical activity (PA) and fitness with hearing impaired (HI) children. Hence, the purpose of our investigation was to evaluate the ability of social cognitive variables (e.g., selfefficacy and social support), environmental (i.e., time outside) and affective constructs (e.g., physical activity enjoyment) to predict PA. Children from the Czech Republic and the USA (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The age range of participants was between 5 and 17 years, with the smallest mean age 9.8 ± 2 years ( Palisano et al, 2011 ), and the largest mean age 17.4 ± 3.7 years ( Puce et al, 2019 ). There were 15 cross-sectional studies ( Batey et al, 2014 , Fiorilli et al, 2016 , Giese et al, 2017 , Jin et al, 2018 , Li et al, 2018 , Maher et al, 2015 , Martin et al, 2013 , Ng et al, 2014 , Puce et al, 2019 , Te Velde et al, 2018 , Shikako-Thomas et al, 2013 , Whitney et al, 2019a , Whitney et al, 2019b , Gür et al, 2020 , Gallego-Méndez et al, 2020 ), one longitudinal study ( Gawrilow et al, 2016 ), and two cohort studies ( Brunes et al, 2015 , PALISANO et al, 2011 ). The included studies were conducted mainly in Western countries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The age range of participants was between 5 and 17 years, with the smallest mean age 9.8 ± 2 years ( Palisano et al, 2011 ), and the largest mean age 17.4 ± 3.7 years ( Puce et al, 2019 ). There were 15 cross-sectional studies ( Batey et al, 2014 , Fiorilli et al, 2016 , Giese et al, 2017 , Jin et al, 2018 , Li et al, 2018 , Maher et al, 2015 , Martin et al, 2013 , Ng et al, 2014 , Puce et al, 2019 , Te Velde et al, 2018 , Shikako-Thomas et al, 2013 , Whitney et al, 2019a , Whitney et al, 2019b , Gür et al, 2020 , Gallego-Méndez et al, 2020 ), one longitudinal study ( Gawrilow et al, 2016 ), and two cohort studies ( Brunes et al, 2015 , PALISANO et al, 2011 ). The included studies were conducted mainly in Western countries.…”
Section: Resultsmentioning
confidence: 99%
“…Sedentary behavior may lead to less PA time, excessive screen-based media exposure, social isolation, and feelings of loneliness, resulting in mental health problems ( Rodriguez-Ayllon et al, 2019 ). Previous studies have shown that PA is positively associated with mental health such as enjoyment ( Jin et al, 2018 , Martin et al, 2013 , PALISANO et al, 2011 ), self-perception ( Batey et al, 2014 , Li et al, 2018 , Martin et al, 2013 , Ng et al, 2014 , Te Velde et al, 2018 ), and mental wellness ( Brunes et al, 2015 , Giese et al, 2017 , Puce et al, 2019 ); and is negatively associated with anxiety and depression ( Brunes et al, 2015 , Fiorilli et al, 2016 , Gawrilow et al, 2016 , Whitney et al, 2019a , Whitney et al, 2019b ) and fatigue ( Maher et al, 2015 ) in children with SEN. The strength of the associations varies according to different PA types.…”
Section: Introductionmentioning
confidence: 95%
“…An overall PA score was calculated by summing the frequencies within each intensity category, multiplying these frequencies by their respective metabolic equivalents (3 for mild, 5 for moderate, and 9 for strenuous), and then summing the three intensity categories. The GLTEQ was used because it is brief, easy to administer, and has been used with similar aged minority children in past research (e.g., Martin, Shapiro, & Prokesova, 2013). Scores on this inventory have produced high reliability coefficients with similar samples (e.g., Martin, McCaughty, & Shen, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Participants reported their level of confidence to overcome common PA barriers by responding to 8 items. These items have been commonly used to assess barrier self-efficacy among youth with disabilities (Martin et al, 2013). A sample item was, "How confident are you in participating in physical activity that makes you breathe hard or feel tired when you have a lot of homework to do."…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation